A copula-based approach to financial contagion in the foreign exchange markets. (12th October 2011) - Jayech, Selma; Ben Zina, Naceur
In this paper, we try to find out if the foreign exchange markets of developed countries reflect the effects of financial contagion of the 2007 subprime financial crisis and the intensity of contagion differs across countries. In fact, we have defined contagion as the significant increase in co-movement of foreign exchange markets during the crisis period for reasons that are not explained by fundamentals. This paper investigates the dependence structure between the following three foreign exchange currencies (the British pound, the French franc and the German mark) by using copulas. Our results suggest that the current crisis does not affect the exchange markets of these three developed countries.